IN VITRO PROPAGATION OF STAHLIANTHUS CAMPANULATUS KUNTZE, A RARE PLANT SPECIES FROM THAILAND - W. Mongkolsawat; S. Saensouk; C. Maknoi; P. Saensouk (Journal of Animal and Plant Sciences, 2018)
A study was conducted to determine the effect of plant growth regulators on the initiation and growth of Stahlianthus campanulatus Kuntze, a rare plant species from Thailand. Rhizome buds derived from shoots were cut and cultured on modified MS medium supplemented with various concentrations of auxin, cytokinin and their combinations. The cultures were kept under a temperature of 25±2 °C with fluorescent light for a 16 hours photoperiod/day for 12 weeks. Multiple shoots cultured on MS medium supplemented with 4 mgL-1 BAP, produced the highest number of shoots per explant (5 shoots/explant). The highest lengths of shoots, 20.20, 20.06 and 20.12 cm, were obtained on the MS medium supplemented with 4 mgL-1 kinetin, 2 and 4 mgL-1 BAP, respectively. The best rooting was observed in MS medium supplemented with 1, 2 and 4 mgL-1 kinetin, which produced 32.40-37.50 roots per shoot. MS medium supplemented with a combination of 4 mgL-1 kinetin and 0.5 mgL-1 IAA gave an average number of 3.0 shoots per explant with a length of 21.28 cm. Acclimatization was successful when transplanted in soil and coconut fiber with 91.6% survivability potential.
Keywords: Stahlianthus campanulatus; Propagation; Zingiberaceae; Rare Plant; Plant Tissue Culture